Biotin and Thiamine Responsive Basal Ganglia Disease – A vital differential diagnosis in infants with severe encephalopathy. (May 2016) - Ygberg, Sofia; Naess, Karin; Eriksson, Mats; Stranneheim, Henrik; Lesko, Nicole; Barbaro, Michela; Wibom, Rolf; Wang, Chen; Wedell, Anna; Wickström, Ronny
Abstract: We report two siblings of Swedish origin with infantile Biotin and Thiamine Responsive Basal Ganglia Disease (BTRBG). Case report: Initial symptoms were in both cases lethargia, with reduced contact and poor feeding from the age of 5 weeks. Magnetic resonance imaging showed altered signal in the basal ganglia, along with grey and white matter abnormalities. The diagnosis BTRBG was not recognized in the first sibling who died at the age of 8 weeks. The second sibling was started on biotin and thiamine immediately upon development of symptoms, leading to clinical improvement and partial reversion of the magnetic resonance imaging findings. Genetic analysis of the SLC19A3 gene identified two mutations, c.74dupT and c.1403delA, carried in compound heterozygous form in both boys, each inherited from one parent. Comments: The first mutation has previously been described in children with BTRBG, and the second mutation is novel. Although the clinical picture in BTRGB is very severe it is also rather unspecific and the diagnosis may be missed. Conclusion: This report highlights the importance of considering biotin and thiamine treatment also in a European infant born to non-consanguineous parents, who presents with symptoms of acute/subacute encephalopathy. Highlights: Encephalopathy in children may be caused by Biotin and Thiamine Responsive Basal Ganglia Disease (BTRBG). Many cases of BTRBG are due to mutations in a thiamine transporter (SLC19A3). Thiamine can in many cases reduce morbidity and mortality. Thiamine treatment should be initiated promptly if BTRBG is suspected.